Approaches to understanding migration: A multi-country analysis of the push and pull migration trend - Bilal Khalid; Mariusz Urbański (Economics & Sociology, 2021)
The study explores the factors that drive migration to Poland and Thailand. It investigated how economic, political, environmental, and social factors impact on workers decision to migrate in search of greener pastures. The research is hinged on the Push-Pull Migration Model. The research populations consisted of a total of 762 purposively selected respondents; 452 were selected from Bangkok and Phuket, Thailand, while 310 were selected from Warsaw in Poland. The study was quantitative research that applied SEM analysis for data interpretation. Findings indicated that 76% of the migrants to Thailand have at least a university degree compared to 24% with a high school certificate or less, while for Poland, 68% have at least a university degree compared to 32% with a high school certificate or less. SEM analysis revealed that only the economic push and pull factors were accepted in both Thailand and Poland/ The results reinforced the significant influence of unemployment, poverty, high employment, and high wages, while acknowledging the impact of political and social factors. The significance of environmental factors from the findings was underwhelming.
Keywords: Migration and Labor Dynamics; Climate Change, Adaptation, Migration; Migration, Refugees, and Integration